The Role Of Kinesics In Teaching Indonesian Language To Foreign Speakers At Ho Chi Minh City University Vietnam - Betrisyia Mawardani Darmawan; M. Isnaini (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
The teaching of Indonesian for Foreign Speakers (BIPA) in international settings faces challenges arising from learners' limited initial linguistic competence as well as differences in linguistic and cultural background. Such conditions require the use of learning strategies that can effectively support the comprehension of meaning. This study aims to examine the role of kinesics as a form of nonverbal communication in the teaching of Indonesian for Foreign Speakers at Ho Chi Minh Open University, Vietnam. This research employs a qualitative descriptive method with interviews as the primary technique. Data collection techniques include interviews, observation, and documentation. The findings indicate that the application of kinesics plays a significant role in the learning process. The use of body movement, gestures, facial expressions, and eye contact has been shown to help learners understand the meaning of utterances and instructional content, as well as to increase engagement throughout the learning process. Accordingly, kinesics can be regarded as a supportive strategy in the teaching of Indonesian for Foreign Speakers and is relevant for application within the context of cross-cultural language learning.